Modeling and optimization of process parametric interaction during high-rate anaerobic digestion of recycled paper mill wastewater using the response surface methodology. Issue 1 (19th January 2022) - Zwain, Haider M.; Barghash, Hind; Vakili, Mohammadtaghi; Sh. Majdi, Hasan; Dahlan, Irvan
Abstract: This study carried out the anaerobic digestion of recycled paper mill wastewater (RPMW) in a high-rate novel anaerobic baffled reactor. The parametric interaction between influent chemical oxygen demand (CODin ) and hydraulic retention time (HRT) was modeled, and process responses were optimized by the response surface methodology (RSM) using a three-level factorial design. The results showed that the optimal condition was determined at CODin of 4, 000 mg/L and HRT of 2 days and predicted values for COD removal, biochemical oxygen demand (BOD) removal, lignin removal, CH4 content, and CH4 production were found to be 94%, 98%, 68%, 85%, and 20.8 L CH4 /d, respectively. According to the statistical analysis of the RSM, all models were significant with very low probability values (from 0.0045 to <0.0001). The parametric interaction showed that increasing the CODin positively influenced the COD, BOD, and lignin removal efficiencies, effluent alkalinity, and methane content and production but was unfavorable for pH and effluent volatile fatty acid (VFA). Shortening the HRT negatively affected the COD, BOD, and lignin removal efficiencies, pH level, alkalinity, and methane content and production, and increased the VFA effluent concentration. The optimal conditions were established at 4, 000 mg/L COD and HRT of 2 days, corresponding to the predicted COD, BOD, and lignin removal efficiencies of 91, 98, and 71%, respectively, whereas 28 mg/L of VFA and 0.125 L of CH4 /g CODremoved were generated. HIGHLIGHTS: RPMW was anaerobically treated using an HR-NABR. The parametric interaction of CODin and HRT and their effects on the HR-NABR performance were modeled using the RSM. The optimal conditions were established at 4, 000 mg/L COD and HRT of 2 days.